Theoretical study of specific heat capacity of thermoelectric half-Heusler XNiSb (X = Sc, Tm) compounds. (3rd April 2021) - Eser, Erhan; Koç, Hüseyin
ABSTRACT: The specific heat capacity of half-Heusler ScNiSb and TmNiSb compounds have been calculated using a simple approximation in the temperature range 0–298 K. The results obtained for the specific heat capacities are in good agreement with the experimental data in the literature. The Debye temperatures were derived by fitting the analytical expression obtained in this study to experimental data. The Debye temperatures and the Sommerfeld coefficients resulting from the fitting are 355.95 K and 7.19 mJ/mol.K for ScNiSb, and 234.5 K and 14.92 mJ/mol.K for TmNiSb.